CD47 expression in solid tumors correlates with phagocytic tumor-associated macrophage gene signature - van Buuren, Nicholas; Xu, Mengshu; Zhang, Yi; Correa, Paola; Zaboli, Shiva; Madjidi, Azadeh; Moon, Christina; Liu, Szu-Wen; Li, Ruidong; Sun, Kai-Hui; Iqbal, Shahed; Aggarwal, Abhishek; et al. (Frontiers in Immunology, 2025)
BackgroundCD47 is a “don’t eat me” signal that is overexpressed in tumors to evade phagocytosis by tumor associated macrophages (TAM). Investigational agents targeting CD47, such as magrolimab, aim to induce phagocytosis of tumor cells by TAMs. Previously, two key TAM subsets have been identified: C1QC TAMs, which display pro-phagocytic activity, and SPP1 TAMs that express pro-angiogenic markers. We characterize CD47 expression and its relationship with tumor macrophages in solid tumor samples.Patients and methodsResectable tumors from head and neck squamous cell carcinoma (n=36) (HNSCC), breast cancer (n=37) (BC), and colorectal cancer (n=36) (CRC) were evaluated for CD47 expression by immunohistochemistry (IHC), two multiplex immunofluorescence panels were used to characterize TAM markers and T cell markers. RNA sequencing was also performed.ResultsCD47 protein expression was higher on tumor cells compared to stromal cells across tumor indications tested. Although CRC had the lowest prevalence for CD47 expression in primary tumors, we observed a marked increase in CD47 expression in CRC liver metastases. We developed an SPP1 TAM gene signature and validated a C1QC TAM gene signature to estimate TAM abundances from bulk RNA-Seq data. In the TAM mIF analysis, HNSCC had the highest macrophage density of the indications tested. We observed a positive correlation between a higher C1QC: SPP1 TAM ratio and macrophage phenotype and tumor T cell density. C1QC macrophage signatures correlate with tumor CD47 protein expression in BC and HNSCC samples, suggesting interplay between them.ConclusionsWe characterized CD47 expression across key solid tumor indications being evaluated clinically using anti-CD47 blockade agents: HNSCC, breast cancer and CRC. Using a CD47 IHC assay, we identified HNSCC as an indication with the highest CD47 expression. In addition, we quantified tumor macrophages using multiplex immunofluorescence (mIF) and determined that HNSCC had the highest density of TAMs. Compared to relatively low CD47 expression in primary CRC tumors, CRC liver metastases had very high CD47 expression. Quantification of TAM signatures and CD47 expression represent key biomarkers to monitor in patient samples during exploration of CD47-blockade agents in the clinic.